English Language Anxiety and Social Competence among Secondary School Students - Praveen G., Manoj; M., Liji (JOURNAL OF INDIAN EDUCATION, 2018)
Due to English language anxiety, students experience tension, nervousness, or sometimes become shy in the classroom. At times, they become frustrated too. The debilitating levels of anxiety in learning and using the English language can cause students to postpone language study indefinitely and keep themselves away from teachers, peer group, etc. This study reports a significant difference in the English language anxiety in subsamples based on gender, medium of instruction, type of school management and type of syllabus. The study was conducted on a sample of 800 students of Class IX drawn from 16 schools of Kozhikode and Malappuram districts of Kerala. The tools used for the study were the English Language Anxiety Scale and Social Competence Scale. The results were derived using statistical techniques such as percentiles, test of significance of mean difference, Pearson’s Product Moment Correlation and ANOVA. This study also brings out the relationship between English language anxiety and social competence in the total sample and subsamples based on gender, medium of instruction, type of school management and type of syllabus. The major findings affirm that students of Malayalam (regional language) medium have more English language anxiety than the students of English medium. Among English medium students, those of state schools have more English language anxiety than the students of central government schools. The study further revealed significant negative relationship between English language anxiety and social competence for the total sample.